People and Seeds - Picado, Wilson (2010)
This article analyzes the processes of selection and dispersion of seeds and its importance in the development of the agriculture in history. It is a comparative analysis between the emergence of the Neolithic revolution and the development of the Green revolution. It is an interpretative study